Pharmacokinetics of Oral d-Serine in d-Amino Acid Oxidase Knockout Mice - Rais, Rana (The American Society for Pharmacology and Experimental Therapeutics, 2012)
d-Amino acid oxidase (DAAO) catalyzes the oxidative deamination of d-amino acids including d-serine, a full agonist at the glycine modulatory site of the N-methyl-d-aspartate (NMDA) receptor. To evaluate the significance of DAAO-mediated metabolism in the pharmacokinetics of oral d-serine, plasma d-serine levels were measured in both wild-type mice and transgenic mice lacking DAAO. Although d-serine levels were rapidly diminished in wild-type mice (t(½) = 1.2 h), sustained drug levels over the course of 4 h (t(½) > 10 h) were observed in mice lacking DAAO. Coadministration of d-serine with 6-chlorobenzo[d]isoxazol-3-ol (CBIO), a small-molecule DAAO inhibitor, in wild-type mice resulted in the enhancement of plasma d-serine levels, although CBIO seems to have only temporary effects on the plasma d-serine levels due to glucuronidation of the key hydroxyl group. These findings highlight the predominant role of DAAO in the clearance of d-serine from the systemic circulation. Thus, a potent DAAO inhibitor with a longer half-life should be capable of maintaining high plasma d-serine levels over a sustained period of time and might have therapeutic implications for the treatment of schizophrenia.